Unlocking the potential of vocational skills: How vocational high school students' preferences for teachers' use of digital technology influence telecommunication technical skills - Pratiwi, Anisa Ihsanul; Abdullah, Ade Gaffar; Mukhidin, Mukhidin (INVOTEC, 2023)
Digital competence is crucial for teachers to utilize digital technology in the current era of learning. Especially for vocational high school teachers, face the challenge of designing effective learning strategies by harnessing digital technology to enhance students' vocational skills. The research aims to investigate vocational high school students' preferences regarding the use of digital technology by teachers and its influence on their vocational skills in VSAT (Vocational Satellite). While this topic has been rarely studied among vocational high school students, understanding students' perception of teachers' digital competence and its impact on their vocational skills can provide valuable insights into how digital technology usage can enhance vocational skills and better prepare students for success in the workforce. This study employs a quantitative method with descriptive and simple linear regression analysis. Data collection involved distributing questionnaires directly and online through Google Forms, which were voluntarily filled out by 123 students from three SMKs in the Bandung and Cimahi regions. The research findings reveal that students' preferences for teachers' use of digital technology fall under the good category, with an assessment interval of 78.2%. Additionally, a positive influence is found between vocational high school students' preferences for teachers' use of digital technology and their vocational skills in VSAT. The study is expected to provide valuable input for teachers and schools to implement teaching methods that support the development of students' vocational skills through optimal utilization of digital technology.